2021
DOI: 10.1096/fj.202002615rr
|View full text |Cite
|
Sign up to set email alerts
|

Low abundance of Mfn2 protein correlates with reduced mitochondria‐SR juxtaposition and mitochondrial cristae density in human men skeletal muscle: Examining organelle measurements from TEM images

Abstract: The role of mitofusin 2 (Mfn2) in the regulation of skeletal muscle (SM) mitochondriasarcoplasmic (SR) juxtaposition, mitochondrial morphology, mitochondrial cristae density (MCD), and SM quality has not been studied in humans. In in vitro studies, whether Mfn2 increases or decreases mitochondria-SR juxtaposition remains controversial. Transmission electron microscopy (TEM) images are commonly used to measure the organelle juxtaposition, but the measurements are performed "by-hand," thus potentially leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Once again, similar observations were previously made in the liver, as the postprandial state was associated with reduced mitochondria cristae length through a Mfn2 and Opa1‐dependent mechanism 11 . Finally, we recently showed that a low Mfn2 protein abundance correlates with reduced mitochondria‐SR interactions and mitochondrial cristae density in human skeletal muscle 33 . Our results indicate that the fasting‐feeding transition‐induces mitochondrial dynamics modifications was not accompanied by changes in mitochondrial density as measured by Transmission electron microscopy and mitochondrial complexes density.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Once again, similar observations were previously made in the liver, as the postprandial state was associated with reduced mitochondria cristae length through a Mfn2 and Opa1‐dependent mechanism 11 . Finally, we recently showed that a low Mfn2 protein abundance correlates with reduced mitochondria‐SR interactions and mitochondrial cristae density in human skeletal muscle 33 . Our results indicate that the fasting‐feeding transition‐induces mitochondrial dynamics modifications was not accompanied by changes in mitochondrial density as measured by Transmission electron microscopy and mitochondrial complexes density.…”
Section: Discussionsupporting
confidence: 84%
“…11 Finally, we recently showed that a low Mfn2 protein abundance correlates with reduced mitochondria-SR interactions and mitochondrial cristae density in human skeletal muscle. 33 Our results indicate that the fasting-feeding transition-induces mitochondrial dynamics modifications was not accompanied by changes in mitochondrial density as measured by Transmission electron microscopy and mitochondrial complexes density. The exception was the mitochondrial CV-ATP5A, which decreased after glucose load.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, none of these proteins appear to play a role in the severity of COVID-19. Future studies should measure other proteins that also regulate mitochondrial cristae density, such as MICOS complex like MIC60 (Castro-Sepulveda et al, 2021;Yang et al, 2015). During hospitalization, patients with well-controlled glycemia show lower mortality than patients with poorly controlled glycemia (upper limit of glycemic variability exceeding 10.0 mmol/L) (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sections of 80‐nm were cut, mounted on electron microscopy grids, and examined using a transmission electron microscope (Philips, Tecnai 12 at 80 kV). Mitochondrial density was evaluated as previously described (Castro‐Sepulveda et al, 2021; Castro‐Sepúlveda et al, 2021; Echeverria et al, 2021). Mitochondrial density (%) and size (μm 2 ) were assessed in 4–6 cells per subject, and 3–10 mitochondria per cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation